FPIES: Reviewing the Management of Food Protein-Induced Enterocolitis Syndrome - Neha Khanna; Kirtika Patel (Hindawi Limited, 2016)
Purpose of Review. The aim of this review is to provide a case driven presentation of the presenting features and diagnostic criteria particularly focusing on the management of FPIES. It also summarises the natural history and resolution of cow's milk induced FPIES. Data Sources. OvidSP Database was used to search for literature using the keywords food protein-induced enterocolitis and FPIES. Recent Findings. The diagnosis of FPIES is often delayed following two or more presentations. Symptoms in the acute form include profuse vomiting usually 2-6 hours following ingestion of food. Vomiting may or may not be accompanied by diarrhoea. Management involves removing the causal food protein from diet. There is some concomitance in cow's milk and soya induced FPIES. Hence extensively hydrolysed formula is the milk of choice unless breast-feeding is carried out in which case that should be continued. Summary. FPIES is a complex form of non-IgE mediated food allergy. More awareness and knowledge of the condition are required to prevent misdiagnosis. Early diagnosis and removal of the culprit food protein improve the outcome. Good nutritional advice and clear management plans are important. More multicentre studies are required to reevaluate and produce consistent oral food challenge criteria and guidelines.